ANALISIS KOMPONEN TINGKAT KESEHATAN BANK TERHADAP HARGA SAHAM BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Medyawicesar, Hana; Tarmedi, Eded; Purnamasari, Imas (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study was to analyze the description of Bank Soundness by using RGEC method and influence on stock priceDesign / methodology / approach - Method in this research used descriptive and verification methods. Data that used are secondary data of each Public bank foreign exchange on Indonesia Stock Exchange with analysis technique using multiple linear regression. Sampling in this research use purposive samplingFindings - The result of this research shows that NPL and ROA have positive effect to share price, GCG and NIM have no effect to stock price, LDR and CAR do not have an effect on stock price but regression direction with positive sign showing relationship with stock price.Originality -The difference of this research with previous research is on research object and method, population and research sample, research period, measuring instrument and research result, as well as foreign theory and journal source and foreign book and research result.